Bulfinch's mythology - Bulfinch, Thomas (Modern Library, 1993)
For almost a century and a half, Bulfinch's Mythology has been the text which the great tales of the gods and goddesses, Greek and Roman antiquity, Scandinavian, Celtic, and oriental fables and myths, the age of chivalry has been known. The stories are divided into three sections: The Age of Fable or Stories of Gods and Heroes; The Age of Chivalry, which contains King Arthur and His Knights, The Mabinogeon, and The Knights of English History; The Legends of Charlemagne or The Romance of the Middle Age